THE ROLE OF THE ENGLISH IN GLOBAL COMMUNICATION AND ITS IMPORTANCE IN THE EDUCATION SYSTEM - Shodmonova Dildora Davron qizi (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
In today’s globalizing world, learning foreign languages is becoming increasingly important. Especially English plays a significant role in international communication and is gradually becoming an integral part of the education system.